The concept of entrepreneur of Schumpeter in comparison to Kirzner - Vaz-Curado, Samuel Fernandes Lucena; Mueller, Antony Peter (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
This paper analyzes Schumpeter’s concept of the entrepreneur in comparison to Kirzner and the Austrian School of Economics. For this purpose, the research uses the original German text as the reference, both the first larger edition of 1911 and the later shorter editions (mainly the seventh edition of 1987, which is an unaltered reprint of the fourth edition of 1934). To elaborate on the differences and similarities between Schumpeter and the Austrian approach, the study focuses on the aspects of equilibrium, discovery, speculation, capital, profit, institutions, and development. The analysis shows how the entrepreneur acts as the motor of economic development and how profit and profit expectations serve as the motifs of entrepreneurial action – both for the pioneer of innovation and the imitators. Different from the Austrian School, Schumpeter applies the concept of equilibrium in the neoclassical sense as the starting point of his dynamic analysis. The Schumpeterian entrepreneur is that economic actor who breaks the statics to push the economy toward development, which is not merely economic growth because development signifies that fundamental changes of the economy take place in the process.